A dual-beam coupled system for hybrid galloping and vortex-induced vibration energy harvesting - Li, Zhiqing (2023)
Small wind energy harvesting converts aeroelastic vibration into electricity and can provide independent power supplies for low-power-consumption sensors, which are not convenient for replacing chemical batteries frequently. As wind energy harvesters collect sustainable energy from the ambient environment, they are environmentally friendly and energy saving. The most widely adopted wind-induced vibration mechanisms for designing wind energy harvesters are vortex-induced vibration (VIV) and galloping. VIV-based piezoelectric energy harvesters (VIVPEHs) can stabilize the output voltage at low wind speeds, while galloping-based piezoelectric energy harvesters (GPEHs) can operate at high wind speeds and have wide bandwidths. This paper uses a spring to connect the two traditional wind harvesters to constitute a hybrid wind piezoelectric energy harvester (HWPEH). It is expected that the HWPEH can inherit the advantages of both traditional wind harvesters, i.e., it can reduce the cut-in wind speed, as the traditional VIVPEH, and have a broad working bandwidth, as the traditional GPEH. The effects of the mechanical and circuit parameters on the output voltage and power of the HWPEH are investigated and compared to traditional wind harvesters. It has been found that the aerodynamic behavior of the HWPEH can be customized by changing the masses, stiffnesses, shunt resistances, and damping coefficients. The proposed HWPEH can outperform traditional wind harvesters if the system parameters are well tuned.